Integrasi Konsep 3R (Reduce, Reuse, Recycle) dalam Pembelajaran Seni Rupa:Inovasi Pedagogis menuju Pendidikan Berkelanjutan - Barokah, Awalina; Hartono, Hartono; Rokhman, Fathur; Wagiran, Wagiran (DPPM Universitas Pelita Bangsa, 2025)
This study explores the integration of the 3R concept (Reduce, Reuse, Recycle) into art education as a pedagogical innovation to support sustainable education. The research employed a systematic literature review using the PRISMA framework, analyzing relevant studies published in the last five years. The findings reveal that the application of 3R principles in art activities consistently enhances students’ critical thinking, creativity, and problem-solving skills through the transformation of waste materials into aesthetic and functional artworks. In addition, 3R integration has been proven to strengthen students’ environmental awareness, social responsibility, and ecological consciousness. These results suggest that 3R-based art education not only contributes to the development of soft skills but also supports the achievement of the Sustainable Development Goals (SDGs), particularly in the areas of quality education and environmental sustainability